Cognitive Flexibility and Mental Well-Being in Turkish Adolescents: The Mediating Role of Academic, Social and Emotional Self-Efficacy - Demirtaş, Ayşe Sibel (Anales de Psicología / Annals of Psychology, 2020)
Adolescence is a critical period of growth and development in an individual’s life cycle. Because of the importance of developmental success during this stage, with implications of adult development and positive mental health, the current study aims to investigate the predictor roles of cognitive flexibility and self-efficacy on mental well-being of Turkish adolescents. Moreover, as the association between cognitive flexibility and self-efficacy are considered to have crucial effects on adolescents’ mental well-being, it was supposed that academic, social and emotional self-efficacy could mediate the relation between cognitive flexibility and mental well-being. The participants of the research are comprised of 192 females (%49) and 200 males (%51), a total of 392 high school students who were attending four different high schools enrolled in grades 9–12, in a city of Turkey. Cognitive Flexibility Inventory, The Self-Efficacy Scale for Children and Warwick-Edinburgh Mental Well-Being Scale were applied in data collection. The results showed that cognitive flexibility positively correlated with sub-dimensions of self-efficacy and mental well-being. Also, sub-dimensions of self-efficacy positively correlated with mental well-being. Findings from the mediational model indicated that academic, social and emotional self-efficacy served to mediate the relationship between cognitive flexibility and mental well-being. Research findings were discussed in the light of the literature and some suggestions were proposed for mental health experts and researchers.